Risk and protective factors for post-thrombotic syndrome after deep venous thrombosis - Cucuruz, Beatrix Rita; Kopp, Reinhard; Pfister, Karin; Noppeney, Jeanette; Tripal, Kathrin; Korff, Thomas; Zeman, Florian; Koller, Michael; Noppeney, Thomas (Journal of vascular surgery. Venous and lymphatic disorders, 2020)
Objective - The most frequent complication of deep venous thrombosis (DVT) is post-thrombotic syndrome (PTS). We recently showed inhibition of varicose vein development by atorvastatin and rosuvastatin. The aim of this study was to test the influence of lipid-lowering therapy with statins on PTS development. - Methods - All patients between January 2002 and June 2018 with diagnosed DVT were enrolled in this study and analyzed retrospectively. Documentation was performed using the standardized system M1 (CompuGroup Medical, Koblenz, Germany) throughout the observation period. Patients received therapeutic anticoagulation and compression stockings. In case of recurrent DVT, patients received lifelong therapeutic anticoagulation. All patients received clinical examination and duplex ultrasound evaluation 3 to 6 months after primary diagnosis and annually thereafter. - Results - A total of 579 patients with DVT were enrolled in this study. Of these patients, 414 (71%) developed PTS (337/414 [81%] presented with the mild version; mean Villalta score, 5.79). Risk factors for PTS development were recurrent DVT (P = .001) and malignant disease (P = .001). Protective factors were therapy with platelet aggregation inhibitors (P = .049) and lipid-lowering therapy with statins (P = .001). After multivariable analysis, the only risk factor was recurrent DVT (P = .001), and the only protective factor was lipid-lowering therapy (P = .001). - Conclusions - Post-thrombotic changes might be reduced by lipid-lowering therapy.
Available online 14 December 2019
Gesehen am 16.04.2020